Study of Temperature Changes around Fibres in Super Pulse Thulium Fibre Laser in Vitro Lithotripsy - Tianfu, Ding; Bo, Xiao; Xue, Zeng; Lei, Liang; Chaoyue, Ji; Jianxing, Li (Urology Journal, 2023)
Purpose: To investigate temperature changes around the fibres of the super pulse thulium fibre laser (SP-TFL) during in vitro lithotripsy. Materials and Methods: Stones were placed in the in vitro model. The laser was continuously excited for 180 s; the probe was positioned 5 mm around the fibre; the laser power was set at 10, 15, 20, 25, and 30 W; and the irrigation rate was set at 0, 15, 25, 35 ml/min, using a domestic SP-TFL. The temperature variations around the fibre under different power settings and different irrigation rates were compared. Results: Without irrigation, the temperature around the fibre rapidly reached the safety threshold of 43℃ at 24 s. At irrigation rate 15 ml/min and laser power <15 W, the temperature around the fibre was <43℃. Once the laser power increased to ≥20 W, the temperature around the fibre increased to >43℃ at its lowest plateau. At irrigation rate 25 ml/min and laser power ≤25 W, the temperature around the fibre was <43℃. At irrigation rate 35 ml/min and laser power <30 W, the fibre temperature was <43℃. When laser power was ≥30 W, the fibre temperature was >43℃. Conclusion: In extracorporeal ureteroscope SP-TFL lithotripsy, when the laser power is ≤15 W, ≤25 W, and ≤30 W, the irrigation rate should be maintained at ≥15 ml/min, ≥25 ml/min, and ≥35 ml/min, respectively.